Clinical application of enhanced recovery after surgery in bipolar transurethral vaporization of prostate for benign prostatic hyperplasia - Cai, Xinliang; Yuan, Yuan; Jiang, Lin; Zhu, Yifei; Ji, Ruidong; Wang, Mingchi; Tang, Ruxi; Lu, Zhenquan; Luo, Bingfeng (Frontiers in Surgery, 2025)
ObjectiveTo explore the clinical application of enhanced recovery after surgery (ERAS) in bipolar transurethral vaporization of the prostate (B-TUVP) and its impact on postoperative recovery.MethodsA retrospective analysis was conducted on the clinical data of 212 patients with benign prostatic hyperplasia (BPH) admitted to the Department of Urology of our hospital from January 2019 to December 2024. Among them, 121 patients were managed under an ERAS protocol (ERAS group), and 91 patients received traditional perioperative care (control group). The clinical characteristics included age, mean body mass index (BMI), preoperative comorbidities, prostate volume (PV), preoperative International Prostate Symptom Score (IPSS), preoperative Quality of Life (QoL) score, preoperative urinary flow rate, and urodynamic parameters. Preoperative management, intraoperative management, and postoperative outcomes were compared between the two groups.ResultsThe clinical baseline data showed no significant differences between the two groups. Compared with the control group, the ERAS group had a significantly shorter duration of continuous bladder irrigation, time to first ambulation, and postoperative length of stay (P < 0.001). The total hospitalization costs were also significantly lower in the ERAS group compared to the control group (P < 0.01). There was no significant difference in the incidence of postoperative complications between the two groups.ConclusionThe application of the ERAS protocol in B-TUVP can promote postoperative recovery, reduce the postoperative length of stay, and decrease total hospitalization costs. However, more prospective randomized controlled trials are needed to further validate the feasibility and effectiveness of this protocol.